2020
DOI: 10.1111/acel.13251
|View full text |Cite
|
Sign up to set email alerts
|

Premature aging syndrome showing random chromosome number instabilities with CDC20 mutation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Pathway analysis of CDC20 interacting proteins suggested additional roles of CDC20 outside cell cycle regulation, with a significant enrichment of specific cellular processes, including protein modification, localization and degradation, telomeres regulation, transcription, and other signaling pathways, as Hippo, TGF-β, β-catenin, MAPK (Table S 1 ). Accordingly, it has been recently shown that CDC20 exerts a pivotal role in different cell type-specific biological processes, as ciliary disassembly [ 87 , 88 ], brain development [ 89 , 90 ], necrosis suppression in neural stem cells under catastrophic cellular stresses [ 91 ], tissue homeostasis and cell fate in human keratinocytes [ 92 , 93 ], genomic stability [ 94 , 95 ], aging [ 96 ] and autophagy [ 97 , 98 ] (Fig. 3 A-D).…”
Section: Main Textmentioning
confidence: 99%
“…Pathway analysis of CDC20 interacting proteins suggested additional roles of CDC20 outside cell cycle regulation, with a significant enrichment of specific cellular processes, including protein modification, localization and degradation, telomeres regulation, transcription, and other signaling pathways, as Hippo, TGF-β, β-catenin, MAPK (Table S 1 ). Accordingly, it has been recently shown that CDC20 exerts a pivotal role in different cell type-specific biological processes, as ciliary disassembly [ 87 , 88 ], brain development [ 89 , 90 ], necrosis suppression in neural stem cells under catastrophic cellular stresses [ 91 ], tissue homeostasis and cell fate in human keratinocytes [ 92 , 93 ], genomic stability [ 94 , 95 ], aging [ 96 ] and autophagy [ 97 , 98 ] (Fig. 3 A-D).…”
Section: Main Textmentioning
confidence: 99%
“…12,14,15 Thus, such mutations are rare in human disease, 12,16 and the clinical significance of mutations in CDC20 have been investigated in only a handful of studies in an animal model or human context. [17][18][19][20][21][22][23] Although CDC20 is overexpressed in the majority of human cancers, 16,[24][25][26][27][28][29][30] the involvement of CDC20 mutations in cancer has never been established in humans.…”
mentioning
confidence: 99%
“…12,14,15 Thus, such mutations are rare in human disease, 12,16 and the clinical significance of mutations in CDC20 have been investigated in only a handful of studies in an animal model or human context. [17][18][19][20][21][22][23] Although CDC20 is overexpressed in the majority of human cancers, 16,24-30 the involvement of CDC20 mutations in cancer has never been established in humans.In the current study, we originally sought to identify the underlying genetic causes of familial malignant ovarian germ cell tumors (mOGCTs). We identified 8 families with histories of mOGCT.…”
mentioning
confidence: 99%
“…1 c). Since the human colon cancer cell line HCT116 has two copies of the NBS1 allele and relatively high efficacy of ssODN knock-in 18 , 19 , we transfected both the Cas9-2A-puromycin resistance gene plasmid vector and the ssODN targeting donors into HCT116 cells. After transient puromycin selection for 48 h post-transfection and subsequent culture for 2 weeks, the drug-resistant colonies were isolated, and their genotypes were analyzed by Sca I digestion and direct sequencing of the PCR amplicon of the target locus.…”
Section: Resultsmentioning
confidence: 99%